The relationship between knowledge management practiced and organizatinal decision making / Ismail Hashim and Azroo Mohamad - Hashim, Ismail; Mohamad, Azroo (2010)
This study seeks to determine the relationship between knowledge management (KM) practices with organizational decision making. KM practices have been divided into two parts which are in term of technology and approach. Technologies in KM consist of corporate portal and intranet whereby the approaches in KM are storytelling and benchmarking. The data will be collected at Sharp-Roxy Corporation (M) Sdn Bhd in Sungai Petani. As such KM field is large, complex, and in constant development, this study will include management, organizational goals and operational practices and philosophies, technologies, and strategies.Therefore, it is essential to the organization to identify and fully utilize the existence technologies and approaches of knowledge management which it will help the organization to make a right and precise decision making.